TAFISA AND UNESCO JOINT EFFORT FOR BUILDING CULTURAL CAPITAL THROUGH TRADITIONAL SPORTS. AN ANALYSIS OF THE 5TH WORLD SPORT FOR ALL GAMES - Małgorzata Bronikowska; Bartosz Prabucki (Studia Humanistyczne AGH, 2015)
The aim of this article is to emphasize and acknowledge traditional sports as an important historical and socio-cultural phenomenon. By describing ‘the traditional sports and games movement’ from its organization to some key ideas, the authors show how local and national heritage of physical culture is important to every society. Within the current process of globalization, which touches on not only economic and political domains but also cultural and ethnic ones, people need to be aware of their heritage and identity. Various forms of our own, indigenous physical activity are part of this identity. In this article, the authors show the general background to the current situation of traditional sports in a globalized world, which is the socio-cultural context in which they exist, by describing some examples of these kinds of sports and initiatives all over the world. Afterwards, the focus will turn to a particular event – The 5thWorld Sport for All Games – during which traditional sports and games are played and promoted, showing the existence of this kind of sport as a potentially efficient tool in promoting cultural exchange and preserving heritage in the contemporary world.